2004
DOI: 10.1124/jpet.103.061986
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adenosine A2A Receptor in the Regulation of Gastric Somatostatin Release

Abstract: Adenosine has been demonstrated to inhibit gastric acid secretion. In the rat stomach, this inhibitory effect may be mediated indirectly by increasing the release of somatostatin-like immunoreactivity (SLI). Results show that adenosine analogs augmented SLI release in the isolated vascularly perfused rat stomach. The rank order of potency of the analogs in stimulating SLI release was 2-p- Adenosine has been demonstrated to modulate a variety of physiological functions by acting on purinergic P1 receptors. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…The concentration of the drug solution and the rate of the drug infusion pump were calculated to achieve the desired final drug concentration that reached the stomach. The final concentration of dimethyl sulfoxide in the perfusate was less than 0.5%, which has been shown not to alter gastric peptide release (Yip and Kwok, 2004). Termination of drug infusion was achieved by disconnecting the drug solution syringe from the aortic cannula and stopping the drug infusion pump.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of the drug solution and the rate of the drug infusion pump were calculated to achieve the desired final drug concentration that reached the stomach. The final concentration of dimethyl sulfoxide in the perfusate was less than 0.5%, which has been shown not to alter gastric peptide release (Yip and Kwok, 2004). Termination of drug infusion was achieved by disconnecting the drug solution syringe from the aortic cannula and stopping the drug infusion pump.…”
Section: Methodsmentioning
confidence: 99%
“…The abundance of adenosine receptors in the stomach suggests that adenosine may play a role in regulating the release of various gastric peptides (Yip and Kwok, 2004;Yip et al, 2004a,b;Yang et al, 2009). We have demonstrated previously that adenosine stimulates somatostatin release via activation of A 2A receptors in both the rat stomach (Yip and Kwok, 2004) and the mouse stomach (Yang et al, 2009) and inhibits gastrin release via activation of the A 1 receptors in the rat stomach (Yip et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was later shown that adenosine may suppress immunoreactive gastrin release by activating A 1 receptors on G cells, leading to inhibition of gastric acid secretion [739]. Adenosine may also act via A 2A receptors to augment somatostatin release and consequently influence gastric acid secretion [732,738].…”
Section: Gastric Acid Secretionmentioning
confidence: 99%
“…A1/gastrin release In the stomach, adenosine protects against stress-induced gastric ulcer formation by inhibiting gastric acid secretion by direct action on parietal cells in some species (guinea pigs and dogs, [42,48]) but not others (rats, [86] [123,125].…”
Section: Purinergic Regulation Of Secretion From Neuroendocrine Cellsmentioning
confidence: 99%